New essays on singular thought - Jeshion, Robin (Oxford : Oxford University Press, 2010)
Leading philosophers present essays on an issue central to philosophy of mind, language, and perception: the nature of our thought about the external world. The essays explore directions for future research, an important resource for anyone working at the interface of semantics and mental representation.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Thought and thinking; Philosophy of mind